2016
DOI: 10.15835/buasvmcn-fst:12329
|View full text |Cite
|
Sign up to set email alerts
|

Romanian knowledge and attitudes regarding dietary fibers

Abstract: Presently, the scientists recognize the health benefits of food fibers in the menu and also plant food sources are at high interest both for general population and food companies. The food companies are responsible for a clear nutrition labelling that will assist consumers to make informed and healthy choices and health providers has to inform the population about the benefits of fibers.The aim of our study was to evaluate the Romanian knowledge and attitudes regarding dietary fibers from food products. We mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…Girls are more concerned with their body image, and increased obesity and overweight in industrialized countries have led to increased dissatisfaction with their bodies. There is a significant downward trend of breakfast eating among pupils from the ages of 11 to 13 years with only 55.5% of students taking breakfast, 63.2% consuming lunch, and 56.7% having dinner on a regular basis [10][11][12]. A similar trend was reported in the current study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Girls are more concerned with their body image, and increased obesity and overweight in industrialized countries have led to increased dissatisfaction with their bodies. There is a significant downward trend of breakfast eating among pupils from the ages of 11 to 13 years with only 55.5% of students taking breakfast, 63.2% consuming lunch, and 56.7% having dinner on a regular basis [10][11][12]. A similar trend was reported in the current study.…”
Section: Discussionsupporting
confidence: 83%
“…In agreement with similar recent studies, teenagers are not interested in the information on food labels, and they do not count foods calories. Contrarily, they are receptive to lectures, competitions, applications regarding proper diet and weight maintaining methods [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Females seem to be more aware of the relation between dietary fiber consumption and prevention of metabolic diseases such as obesity, type 2 diabetes and overall health status (Table 3). This is in line with study of Tarcea et al [23] which demonstrated more females than males responding correctly to the favorable role of fiber in cardiovascular safety, regulating blood sugar, reducing risk for obesity, etc. This supports our results, which may mainly be attributed to the greater involvement of females in food choice for their family [32] and a greater care for their own appearance [33].…”
Section: Discussionsupporting
confidence: 92%
“…The study reported that the knowledge of fiber consumption varied depending on age, gender, education level, and location (rural versus urban) [22]. Similar results from Romania demonstrated the vital role of knowledge, information and community intervention regarding fiber intake and its role in health status [23]. Thus, nutrition education and health awareness programs are preferred choices to educate societies to develop proper dietary habits.…”
Section: Introductionmentioning
confidence: 71%